2014
DOI: 10.1177/0883073814530500
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Suppresses Hypoxic-Ischemic Brain Damage in Newborn Rats

Abstract: The optimal therapeutic time-window and protective mechanism of hyperbaric oxygen in hypoxic-ischemic brain damage remain unclear. This study aimed to determine the neuroprotective effects of hyperbaric oxygen. Following hypoxic-ischemic brain damage modeling in neonatal rats, hyperbaric oxygen was administered at 6, 24, 48, and 72 hours and 1 week after hypoxia, respectively, once daily for 1 week. Fourteen days after hypoxic-ischemic brain damage, cell density and apoptosis rate, number of Fas-L+, caspase-8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…There are many factors that cause aging, including telomere shortening, oncogene activation, and DNA damage caused by reactive oxygen species (ROS), among which the most critical factor is the imbalance of oxygen free radical metabolism [ 2 ]. Free radical theory holds that because of the imbalance of free radical metabolism, the structure and function of tissues and organs are in disorder, which causes the body aging [ 3 ]. There are two signaling pathways associated with aging, p53-p21-Rb pathway and p16-pRb pathway [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that cause aging, including telomere shortening, oncogene activation, and DNA damage caused by reactive oxygen species (ROS), among which the most critical factor is the imbalance of oxygen free radical metabolism [ 2 ]. Free radical theory holds that because of the imbalance of free radical metabolism, the structure and function of tissues and organs are in disorder, which causes the body aging [ 3 ]. There are two signaling pathways associated with aging, p53-p21-Rb pathway and p16-pRb pathway [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous protocols (14,15), the rats in the HBO group and HIBD+HBO group were placed into a hyperbaric chamber (model YLC 0.5/1A baby hyperbaric chamber; China State Shipbuilding Corporation 701, Beijing, China) 24 h after surgery and were administered HBO treatment (100% oxygen under 0.02 MPa for 30 min). The pressure gradually reached a maximum of 0.02 MPa in 15 min, which was maintain for another 30 min, and gradually reduced to normal.…”
Section: Preparation For Animal Model and Groupingmentioning
confidence: 99%
“…Previous studies have demonstrated that there is an optimal therapeutic time frame for HBO treatment in neonatal rats with hypoxic-ischemic brain damage (78–80). However, to the best of our knowledge, the optimal timing of treatment for patients with brain injury remains unknown.…”
Section: Discussionmentioning
confidence: 99%